Action Plan Curriculum Freedom To Learn- Independent Campus Field Social Science Islamic Higher Education Institution (PTKIN) In Indonesia - Nursapia Harahap (CV. AFDIFAL MAJU BERKAH, 2022)
This study aims to study and analyze how it works, and the timely achievement of targets for implementing the independent curriculum for learning independent campuses at Islamic religious colleges in Indonesia. This research was conducted with a descriptive qualitative approach using SWOT analysis: Strengths (S), Weaknesses (W), Opportunities (O) and Threats (T). The results of this study indicate that PTKIN's strength is as an extension of the government and collaborating in managing universities funded by the state through the ministry of religion. However, the budget provided cannot be managed properly due to a lack of human resources, both in the field of management and technology that has the ability to manage an efficient and effective learning system and is coordinated with other institutions. The economic condition of students, who are on average lower middle class, becomes an obstacle in implementing the Merdeka Learning Curriculum at the Merdeka Campus. The readiness of the incumbents to collaborate with the industrial sector has not been maximized, so that students cannot be distributed to various companies or industries and existing government institutions/agencies. The leadership's inability to build networks with the industrial world and other institutions/agencies will give birth to alumni who are not professional and competent in their fields.